High resolution radar for automobile applications - R. Schneider; J., Wenger (Advances in Radio Science, 2003)
This contribution points out the potential of radar sensors with high resolution in azimuth and range in traffic environment and addresses some aspects of their practical implementation with respect to system design, hardware and software. A prototypical vehicle-based instrumentation radar is presented, which performs on-line acquisition and real-time visualisation of radar images with an update rate of up to 10 Hz. The enhanced perception capabilities of high resolution radar in traffic environment will be demonstrated with respect to new comfort and safety features, and practical realisation approaches concerning data processing and hardware including the scanning antenna will be discussed.